2013
DOI: 10.1111/jocn.12065
|View full text |Cite
|
Sign up to set email alerts
|

Family needs and involvement in the intensive care unit: a literature review

Abstract: Meeting Intensive Care Unit family needs can be achieved by supporting and involving families in the care of the critically ill family member. More emphasis should be placed on identifying the family needs in relation to the influence of cultural values and religion held by the family members and the organisational climate and culture of the working area in the Intensive Care Unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
1
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(135 citation statements)
references
References 38 publications
2
119
1
13
Order By: Relevance
“…7,8 Family members of critically ill patients consistently identify the need for information and the need for reassurance as the highest priority needs during an ICU hospitalization, yet the need for information is often unmet. [9][10][11] Furthermore, the ICU is a unique setting where patients and family members are coping with stress, 12,13 and they need useful, real-time information adapted to the critically ill patient's anxiety. 2 Delivery of information should be sensitive to the patient and families' current needs, recognizing that some patients report increased anxiety when information is shared before they are ready to receive it.…”
mentioning
confidence: 99%
“…7,8 Family members of critically ill patients consistently identify the need for information and the need for reassurance as the highest priority needs during an ICU hospitalization, yet the need for information is often unmet. [9][10][11] Furthermore, the ICU is a unique setting where patients and family members are coping with stress, 12,13 and they need useful, real-time information adapted to the critically ill patient's anxiety. 2 Delivery of information should be sensitive to the patient and families' current needs, recognizing that some patients report increased anxiety when information is shared before they are ready to receive it.…”
mentioning
confidence: 99%
“…Further to this, the most important proximal need of family members was to see the patient frequently. & Clerehan et al (2013), argued that restricted visitation practices in critical care in Saudi Arabia are based on tradition rather than evidence and the findings of their study revealed that family members prefer flexible visiting practices. Davidson, Powers, Hedyat, Tieszen, Kon et al (2007) expressed that restricted visiting hours decreases family member satisfaction as this prevents them from obtaining information regarding the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Angehörige von Intensivpatienten 1 haben ein hohes Informationsbedürfnis [1]. Fehlende Information kann zu Schlafstö-rungen, Angst und Stress führen [2][3][4][5][6][7].…”
Section: Hintergrund Und Fragestellungunclassified